(3fXe Ydhe GdMOjKs - (3GdNhjj , TgGH GdOjf CHh YHO Gddg eMeO Hf CMeO Hf Ndjd Hf SYGOI GdNhjj,J (B693 (3g` s ((3eMeO Hf eMeO Hf YHO GdefYe GdCfUGQi s)
(3ChdgG (B:s
(3GdMeO Gddg GdPi gOGfG HCMeO CYdi GdhQi ecGfG hNUg HCHdZ GdJaVjd Udi Ydjg Gddg ef QShd s
(3BNQgG (B:s
(3BNQ fXe Ydhe GdMOjK hGdMeO ddg hMOgq s
(3GSe GdeDda Ydi dhMI GdYfhGf(B: (3TeS GdOjf CHh GdYHGS CMeO Hf SYGOI GdNhdis
(3hgh NWCs
(3fXeg UGMHg SfI (B691 (3g`s
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs